2008
DOI: 10.1002/jmri.21508
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of diffusion‐weighted magnetic resonance imaging of the pancreas: Usefulness in characterizing solid pancreatic masses

Abstract: Purpose:To evaluate whether measurement of apparent diffusion coefficient (ADC) and pure diffusion coefficient (D) can help to characterize solid pancreatic masses. Materials and Methods:Diffusion-weighted MR imaging was performed in both a patient group (n ϭ 71; pancreatic cancer [n ϭ 47], mass-forming pancreatitis [n ϭ 13], solid pseudopapillary neoplasm [n ϭ 6], and neuroendocrine tumor [n ϭ 5]) and a normal control group (n ϭ 11) by applying three b-factors of 0, 500, and 1000 sec/mm 2 . ADC 500 , ADC 1000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
159
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(171 citation statements)
references
References 34 publications
(72 reference statements)
9
159
3
Order By: Relevance
“…In the study by Liapi et al [40] , ADC values rose concomitantly with response to transarterial chemoembolization (TACE), in tandem with decreased enhancement of the treated lesions. For the primary lesions, DWI may allow for preoperative localization of tumors in the pancreas, especially those which do not demonstrate the typical hypervascular pattern [41,42] .…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…In the study by Liapi et al [40] , ADC values rose concomitantly with response to transarterial chemoembolization (TACE), in tandem with decreased enhancement of the treated lesions. For the primary lesions, DWI may allow for preoperative localization of tumors in the pancreas, especially those which do not demonstrate the typical hypervascular pattern [41,42] .…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…The same radiologist performed the ROI measurement of the ADC values of the target lesions on DW images using MATLAB-based software (blinded), which automatically calculates ADC values of the areas within manually drawn ROIs [18]. For each target lesion, the ROI was placed in the same manner as the ROI measurement of the SI of the target lesion.…”
Section: Quantitative Image Analysismentioning
confidence: 99%
“…Park et al (25) observed that high perfusion in pancreatic cancer detected on DCE-CT was associated with increased response to chemoradiotherapy. Also, the role of DCE magnetic resonance imaging has evolved in the field of perfusion imaging, and several groups have used it in evaluating the perfusion of benign and malignant pancreatic lesions (10,(26)(27)(28). Nevertheless, [ 15 O]H 2 O PET has been studied more extensively than either DCE-CT or magnetic resonance imaging, and is regarded by some authors as a gold standard in perfusion imaging (15).…”
Section: O]h 2 O and [mentioning
confidence: 99%